Does Customary Law Discriminate Balinese Women’s Inheritance Rights? - Hanna Christine Ndun; Sarah Suttor; I Gusti Agung Ayu Dike Widhiyaastuti (Faculty of law Udayana University, 2018)
There is a stereotype with regard to the rights of the Balinese women on inheriting under the Balinese tradi-tional customary law. It is generally assumed that the law discriminates Balinese women as well as against the human rights principle of equality. This article analyzes the contemporary problems of such issue and would demonstrate the actual principles, rules and practices, including the essential concept of the rights under the Balinese traditional customary law of inheritance. This issue has been explored under a normative legal approach where the resources are primarily taken from the relevant national legal instruments and court decisions, instead of textbooks and journals. An interview has also been commenced for clarifying some aspects of the issue. This article concludes that there has been a generally misleading on viewing the Balinese customary law as discriminating women on an inheritance issue, as in fact, the law also provides rules for supporting women’s rights for inheriting. The law in a certain way has properly preserved the right of women for inheriting in which women under the law have also enjoyed rights for inheriting, especially the daughter and widow. In contrast, the Balinese men that are generally perceived as the ultimate gender enjoying privileges rights to inherit, in the practice of inheritance in the traditional community are also subject to some discrimination. The law has provided a set of rule of inheritance both for men and women where they are subject to certain equal rule and condition. The law also clarifies that both genders are enjoying equal rights on inheritance in a certain portion and situation binding under the principle of balancing between rights and obligation for each side.